Phytochemicals and bioactivities of Curcuma mangga Valeton and Van Zijp., Boesembergia prainiana (King ex Baker) Schltr. and Bauhinia thonningii Schumach. & Thonn - Mohammad Noor, Halimatul Saadiah (2014)
Phytochemical and bioactivity studied on three medicinal plants, Curcuma mangga Val. and Van Zijp., Boesenbergia prainiana (King ex Baker) Schltr. and Bauhinia thonningii Schum. were carried out. Curcuma mangga Val. and Van Zijp. and Boesenbergia prainiana (King ex Baker) Schltr. belong to the family of Zingiberaceae while Bauhinia thonningii Schum. belongs to the family of Cesalpiniaceae. The chemical constituents of these plants were isolated using chromatographic methods while the structure of the compounds were elucidated using various spectroscopics methods including infrared (IR), mass spectrometry (MS) and nuclear magnetic resonance (1H, 13C and 2D NMR). The crude extracts and isolated compounds were screened to biological activity studies which were cytotoxic, antioxidant, total phenolic content, antimicrobial and antifungal. The isolation work on rhizomes of Curcuma mangga have yielded six compounds which were identified as curcumin (4), demethoxycurcumin (5), curcumol (51), curdione (52), zederone (53) and β-sitosterol (22). Curcumol (51), curdione (52) and zederone (53) are reported to be first isolated from this species. For Boesenbergia prainiana, phytochemical studies were first reported on isolation of four compounds which were stigmasterol (54), lupeol (55), lupenone (56) and β-sitosterol (22). Bauhinia thonningii afforded three compounds elucidated as 9-hydroxytridecyl decosanoate (57), betulinic acid (58) and friedelin (59) which also have never been reported previously on this species. Crude extracts and isolated compounds were subjected to cytotoxic screening against five human cancerous cell lines; promyelocytic leukemia (HL-60), breast cancer (MCF-7), colonic cancer (HT-29), cervical cancer (HeLa) and T-lymphoblastic (CEM-SS) using MTT assay. Hexane, chloroform, ethyl acetate and methanol extracts of rhizomes of Curcuma mangga were active against CEM-SS cell line with IC50 value ranging from 11.35 to 15.41 μg/mL. This is the first report on cytotoxic activities towards CEM-SS cell line. The hexane and chloroform extracts were also active against MCF-7, HeLa and HT-29 cell line with IC50 values ranging from 5.75 to 17.9 μg/mL. Isolated compounds,4 and 5 exhibit promising activities against all selected human cancerous cell. IC50 values of Curcumin (4) and demethoxycurcumin (5) against HL-60, MCF-7, HeLa and CEM-SS were ranging from 3.14 to 11.04 μg/mL. Furthurmore, curcumol (51) was strongly active against MCF-7 and HeLa cell lines with IC50 values of 6.84 and 1.25 μg/mL while curdione (52) was active against HT-29 cancer cell line with IC50 of 9.08 μg/mL. In addition, zederone (53) was strongly active against MCF-7 cell line with IC50 of 3.43 μg/mL. For Boesenbergia prainiana, hexane and chloroform extracts were active against MCF-7 cell line with IC50 of 17.54 and 18.26 μg/mL. As for Bauhinia thonningii, hexane, chloroform, ethyl acetate and methanol extracts were strongly active against CEM-SS cell line with IC50 value ranging from 9.21 to 11.12 μg/mL. These cytotoxic properties were also reported for the first time from this species. For antioxidant assay, chloroform, ethyl acetate and methanol extract of Curcuma mangga show strong antioxidant effect with IC50 values of 40.58, 30.17 and 24.97 μg/mL, respectively while no antioxidant effect was observe on all crude extracts of Boesenbergia prainiana. For Bauhinia thonningii, ethyl acetate and methanol extracts show strong antioxidant effect with IC50 values of 40.58 and 24.97 μg/mL. Isolated compounds of Curcuma mangga, curcumin (4) and demethoxycurcumin (5) showed strong antioxidant activity with IC50 values of 26.67 and 31.52 μg/mL respectively. Total phenolic content (TPC) determination indicated chloroform, ethyl acetate and methanol extracts of Curcuma mangga have high TPC followed by ethyl acetate and ethanol extracts of Bauhinia thonningii. In antimicrobial screening test, methanol extract of Curcuma mangga exhibited remarkable antimicrobial activity against Methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa and Bacillus subtillis. For Boesenbergia prainiana,and Bauhinia thonningii, its crude extracts indicated low effect against MRSA, Bacillus subtillis and Pseudomonas aeruginosa. Antimicrobial activity studies have never been reported previously on Boesenbergia prainiana and Bauhinia thonningii.